The Effectiveness of Jarimatika Methods with Tapertis Media on Students’ Multiplication Concept Understanding - Kartika Yuni Purwanti; Ika Silfiana Arifatul Khoiriyah (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2020)
The aim of this research was to prove the effectiveness of the use of Tapertis Media towards the 4 graders of Elementary Schoolsâ€™ multiplication concept understanding. The type of this research is experimental research. Using the intact-group comparison type of pre-experimental design. With 9 students as the sample of this research. Using purposive sampling technique. The methods used were the multiplication concept understanding test, observation, and documentation. Using validity of media expert, validity test, reliability test, normality test, homogeneity test, paired sample T-Test, and regression test for the data analysis. The result showed that Jarimatika with Tapertis media has effectiveness in improving the 4 graders elementary schoolsâ€™ multiplication concept understanding. The result of paired T-Test showed the significance level of < 0.05 is 0.00 < 0.05, then ð»ð‘Ž is accepted. The result of T-test showed that the average of learning achievement of the experimental class was higher than the average of the learning achievement of the control class, and the significance level was < 0.05, then ð»ð‘Ž is accepted. The result of regression test showed that significance value of pre-reading skills is 0.038 where the value is less than 0.05, therefore, the hypothesis is accepted. The data of the multiplication concept understanding value also showed that the learning average of the experimental class was greater than the control class. The data analysis result showed that Jarimatika with Tapertis media has effectiveness in improving the studentsâ€™ multiplication concept understanding.